Second hand or second generation? The performance of secondary buyouts - Jonas Kick; Bernhard Schwetzler (Financial Markets and Portfolio Management, 2024)
Secondary buyouts (SBOs) appear paradoxical because the surge in SBO activity is met with scepticism from the public and investors regarding their performance. In this paper, we undertake a comprehensive analysis of SBO performance through two distinct lenses: First, we address the prevailing notion of SBOs as “lemons”. These are perceived as opportunities that, following a successful primary buyout (PBO), seemingly leave little room for further value creation. To investigate this “negative correlation hypothesis”, we employ a unique back-to-back sample of 276 cases involving the same firm in both a PBO and an SBO. Analysing the correlation between the internal rate of returns (IRRs) of back-to-back PBO/SBOs, our results do not support the “negative correlation hypothesis”. Second, we directly compare the deal performance of the two related back-to-back buyout rounds. For our back-to-back sample, we find that PBOs display significantly higher IRRs than SBOs. However, after performing a matched comparison adjusting for size and holding period differences, which are two well-known pitfalls of IRR rank orders, our findings suggest that there is no systematic outperformance of SBOs against their PBO comparables. Finally, we analyse differences in operating performance between PBOs and SBOs. Our results do not indicate a significant difference, either based on the back-to-back sample or when comparing PBOs and SBOs against matched public peers. In the light of our findings, we advocate for a reevaluation of the current perception of SBOs. Rather than being dismissed as “second-hand” opportunities, they should be recognised as “second-generation” opportunities deserving closer consideration.
Keywords: G23; G24; G32; G34; 330; Private equity; Secondary buyouts; Value creation; IRR; Operating performance